Antimicrobial Activity of Chemical Hop (Humulus lupulus) Compounds: A Systematic Review and Meta-Analysis - Despina Kiofentzoglou; Elisavet M. Andronidou; Panagiota I. Kontou; Pantelis G. Bagos; Georgia G. Braliou (Applied Sciences, 2025)
Humulus lupulus, commonly known as hop, is a climbing plant whose female cones impart beer’s characteristic bitterness and aroma and also serve as a preservative. In this study, we conducted a meta-analysis to investigate the antimicrobial activity of hop compounds and extracts against various microorganisms by statistically synthesizing minimum inhibitory concentration (MIC) values. From the 2553 articles retrieved from the comprehensive literature search, 18 provided data on MIC values for six hop compounds, and three extract types tested against 55 microbial strains’ MIC values corresponded to 24 and 48 h incubation periods with compounds or extracts. The results indicate that xanthohumol (a flavonoid) and lupulone (a bitter acid) exhibit potent antimicrobial activity against most tested microorganisms, particularly food spoilage bacteria [21.92 (95%CI 9.02–34.83), and 12.40 (95%CI 2.66–22.14) μg/mL, respectively, for 24 h of treatment]. Furthermore, hydroalcoholic extracts demonstrated greater efficacy compared to supercritical CO2 (SFE) extracts, which showed limited antimicrobial effects against both probiotic and non-probiotic strains. These findings underscore the need for standardized, evidence-based protocols—including uniform microbial panels and consistent experimental procedures—to reliably evaluate the antimicrobial properties of hop-derived compounds and extracts. Taken together, our findings ultimately chart a path toward evidence based antimicrobial tests that could inform food-preservation strategies and inspire the development of plant-based antimicrobials.